Cambridge Review. (Cambridge [Eng.] Cambridge University Press, 1879)
Volumes 1-26 include a supplement: The University pulpit
Published by the students of Cambridge University
"A journal of university life and thought."
Keywords: University of Cambridge -- Periodicals